2021
DOI: 10.4236/jss.2021.97027
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ TPACK Development: A Review of Literature

Abstract: The TPACK framework describes the kinds of knowledge required by teachers for successful integration of technology in teaching. TPACK is the heart of good teaching and describes the kinds of knowledge needed by a teacher for effective technology integration. In this study, such teachers' TPACK development strategies as Learning by Design Approach, Lesson Study, Microteaching, microteaching lesson study are analyzed after an analysis of the process of TPACK formation and its components. In addition, TPACK devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Following Rahayu's opinion (2022), increasing TPACK capabilities cannot be done partially or individually, only by increasing knowledge or technological ability or content knowledge, or pedagogical knowledge but must be carried out in an integrated manner. This TPACK is at the heart of teaching, which describes the type of knowledge teachers need to integrate effective technology into learning (Zhang & Tang, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Following Rahayu's opinion (2022), increasing TPACK capabilities cannot be done partially or individually, only by increasing knowledge or technological ability or content knowledge, or pedagogical knowledge but must be carried out in an integrated manner. This TPACK is at the heart of teaching, which describes the type of knowledge teachers need to integrate effective technology into learning (Zhang & Tang, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…(3) TPACK questionnaires (Schmidt et al, 2009) ( (Fernández, 2002). Finally, the study of microteaching, which is a combination of LS and microteaching (Zhang and Tang, 2021). These types of TPACK developments are part of studies that are supported by empirical evidence revealed, for example, by Harris (2016) in teachers in service and by Mouza (2016) in teachers in training, allowing the analysis of the training process.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, TPACK has emerged as a focal point in research on technology education and teacher professional development across various disciplines [8,[39][40][41][42]. In the area of STEM education, numerous studies targeting both prospective and in-service teachers have been anchored in the TPACK framework [28,[43][44][45][46][47][48][49][50][51].…”
Section: Literature Reviewmentioning
confidence: 99%